PEMBERDAYAAN EKONOMI MASYARAKAT MELALUI PEMANFAATAN SUMBER DAYA ALAM DI DESA SINAR GADING - Sovia Riza; Awatif (Hira Institute, 2023)
Economic empowerment is an effort to improve people's welfare through activities to increase capacity and independence by involving the community and stakeholders to realize community welfare. Through the utilization of existing natural resources is a form of empowerment based on local potential which strongly supports community development. Good management of natural resources can improve the welfare of local communities. The purpose of this study was to find out how the process of empowering the community's economy through the utilization of natural resources in the village of Sinar Gading. This research uses descriptive and qualitative methods. This research shows that community economic empowerment through the utilization of natural resources in the village of Sinar Gading through the formation of tofu production is very influential in changing the community's economy. Where through this empowerment, the community can developt.